Efeito do uso do solo sobre seus atributos na microrregião de Chapadinha-MA - Pinto, Cristiane Rêgo Oliveira [UNESP] (2014)
The chemical and microbiological properties of the soil can be considered indicators of processes that occur in response to disturbances anthropogenic and can be important variables to predict the quality of agricultural ecosystems. The objective in the present study to evaluate changes in soil attributes, select those with better performance to indicate the quality of soil use and involve chemical and microbiological attributes thereon in soils under five areas belonging to the micro-region of Chapadinha Maranhão state. Soil samples were collected in depth of 0- 0.10 m in different areas (soybean monoculture, alley cropping, cutting and burning, grazing and native forest) for chemical analysis: pH, Al3 +, H + Al, Ca 2+, Mg 2+, K, Na, available P, organic matter (OM), total bases (SB), cation exchange capacity (CEC) and base saturation (V) and attributes microbiological: microbial biomass carbon - CBM, basal respiration, metabolic quotient (qCO2), Microbial quotient (qMIC) and enzymatic activity (desidrogense, cellulase and urease) soil. In the soils are highly the attributes associated MO, CEC, pH and V% between chemistry and dehydrogenase, C-BMS, cellulase and qMIC between microbiological soil attributes. The CTC attributes and MO are shown antagonistic to pH, Pressyne, V% and qMIC. Positive correlations between biological and chemical soil characteristics suggest that land use has encouraged the growth of biomass and stimulated microbial activity, which is efficient in nutrient cycling processes and improved soil quality